Immersive virtual simulation system design for the guidance, navigation and control of unmanned surface vehicles - Huang, Fanghao; Chen, Xuanlin; Xu, Yun; Yang, Xiao; Chen, Zheng (Ocean engineering, 2023)
The simulation of Guidance, Navigation and Control (GNC) is a key issue to provide an economical way to test and improve the various algorithms in the development and research of Unmanned Surface Vehicle (USV). However, most of the existing simulation systems are offline with limited visualization scene, and unable to interact with real sensors mounted on the USV, thus failing to display the immersive and real-time motion of USV for researchers. In this paper, a virtual simulation system is developed, which provides an open and online platform for the immersive and visualized GNC simulation of USVs. Two modes are designed with one to provide a virtual simulation with simulated sensors and USVs, while another to provide a visualization of real GNC tasks driven by the in-situ data. To accomplish these two modes, the lower computer works to interact with simulated or real sensors, and calculate the mathematical model of USVs, while the host computer works to obtain the data from lower computer, and implement the GNC of USVs, which is finally and immersively displayed in the virtual scene. Moreover, an open interface is designed in this system that allows the researchers to test their own algorithms in the GNC of USVs. The sliding mode control (SMC) controller, hybrid navigation algorithm as well as LOS-based formation navigation algorithm are proposed to serve as two case studies in the single-USV and multi-USV scenarios. The results verify the effectiveness of the proposed virtual simulation system in the immersive and visualized simulation of GNC for USVs.